AKULTURASI BUDAYA: Studi Kasus Komunitas Samin di Kudus Jawa Tengah: [CULTURE ACULTURATION: Case Study Samin Community In Kudus Central Java] - Moh Rosyid (Berkala Arkeologi Sangkhakala, 2020)
The purpose of writing this article is to describe the form of cultural acculturation carried out by the Samin community in Kudus, Central Java against the Muslim tradition of Nahdliyin is traditions to response local wisdom and don’t contradicting by syariah. Data obtained by interview, literature review, and observation. Data collection was analyzed using a qualitative descriptive approach. The culture that Samin responded to took the form of a life cycle slogan and circumcision of a boy. Acculturation creates a symbiotic mutualism because people Nahdlatul Ulama is also responsive to local Javanese traditions. The specificity that is still maintained by the Samin community is wearing tokong pants, headbands, all in black for men, and for women wearing a jarit. When attending a marriage and dying. When at home or in the fields, wear other people's usual clothes. There is also a nahdliyin culture that Samin does not respond to because it avoids the similarity of tradition, such as a cap. As for sarong, it is a Samin tradition that is only used when a man marries. The basic principles of nahdliyin in tradition are tawasuth (moderate), tawazun (balance between faith and reality), al i’tidal (upright, not easily provoked), at tasamuh (tolerant). It's just that, the impact of urbanization Samin residents, the culture of the city is also a tradition like polished hair. Senior Samin was powerless to deal with it. If this is not controlled, the culture of the city changes the uniqueness of Samin. Tujuan penulisan artikel ini untuk mendeskripsikan bentuk akulturasi budaya yang dilakukan komunitas Samin di Kudus, Jawa Tengah terhadap tradisi muslim Nahdliyinyakni tradisi yang merespon kearifan lokal dan tidak bertentangan dengan syariat Islam.Data diperoleh dengan wawancara, kajian literatur, dan observasi. Terkumpulnya data dianalisis dengan pendekatan deskriptif kualitatif. Budaya yang direspon Samin berupa slametan daur kehidupan dan khitan anak lelaki. Akulturasi tercipta simbiosis mutualisme karena Nahdliyin juga responsif terhadap tradisi lokal Jawa. Kekhasan yang masih dipertahankan komunitas Samin adalah memakai celana tokong, ikat kepala, berwarna serba hitam bagi lelaki, dan bagi perempuan memakai jarit. Bila menghadiri perkawinan dan melayat kematian. Bila di rumah atau di sawah memakai pakaian lazimnya warga lain. Ada pula budaya nahdliyin yang tidak direspon Samin karena menghindari keserupaan tradisi, seperti berpeci. Adapun bersarung menjadi tradisi Samin yang hanya digunakan ketika lelaki menikah. Prinsip dasar nahdliyin dalam tradisi adalah tawasuth (moderat), tawazun (keseimbangan antara akidah dengan realita), al I’tidal (tegak lurus, tak mudah terprovokasi), at tasamuh (toleran). Hanya saja, imbas urbanisasi warga Samin, budaya kota menjadi tradisinya pula seperti rambut disemir. Senior Samin pun tidak berdaya menghadapinya. Bila hal ini tidak dikendalikan maka budaya kota mengubah kekhasan Samin.